Poverty and green economy in South Africa: What is the nexus? - Omolade Adeleke; Mbonigaba Josue (Cogent Economics & Finance, 2019)
The study investigates the relationship between the green economy and poverty in South Africa from 1990 to 2017. Data on green economy indicators such as share of clean energy, CO2 emissions, human development index, secondary school enrolment, life expectancy at birth and access to electricity are extracted from United Nations Development Programme database, while data on per capita income and percentage of population living below the poverty line, which is used as the dependent variable, are collected from Statistics South Africa. Based on the statistical properties of the data, the Auto-Regressive Distributed Lags approach is used to analyse the short- and long-run influences of the green economy on poverty reduction in South Africa. The results show that the green economy has more of significant long-run impact than short run. It also shows that share of clean energy, CO2 emissions, human development index, secondary school enrolment, life expectancy at birth and access to electricity are the most important green economy indicators that have a significant impact on poverty reduction, while levels of income appear to have a weak impact. As a result, efforts should be more focused on improving the indicators of the green economy and sustainable development in South Africa if the increasing poverty level in the country is to be restrained.
Keywords: O10; O11; O13; 330; Green economy; poverty; clean energy; human development index